Ecofriendly HPLC method for caffeine in dietary supplement determination using ethanol-water mobile phase and PFP-column - Oleksandr Syrotchuk, Olga Glushachenko, Iryna Musienko, Iryna Didukh, Iryna Nizhenkovska (Journal of Applied Pharmaceutical Science, 2023)
Caffeine is a natural alkaloid recognized as an active central nervous system stimulant. This substance can be found in beverages, medicines, and dietary supplements, and its concentration must be controlled to minimize the side effects of overdose. High-performance liquid chromatography is a routine method for caffeine determination that employs the octadecylsilyl stationary phase (SiO2-C18) in combination with methanol and acetonitrile solvents. Unlike the others, we propose applying pentafluotophenyl (SiO2-PFP) stationary phase and water–ethanol mobile phase as an environmentally benign solvent alternative. Due to the additional interactions with the pentafluorophenyl ring of the stationary phase, the separation of caffeine from other compounds, such as theophylline and theobromine, can be significantly improved. Caffeine retained better by 1.5–2 times compared to the C18 column. Chromatographic column discovery F5 (4,6 × 250 mm, 5 μm particle size) was thermostatted at 40°C and gradient elution from 20% to 60% ethanol was used for chromatography. The method was validated for two dietary supplements’ specificity and showed linearity in the range of 5–15 mcg/ml, precision of not more than 2.0%, and accuracy of not more than 1.0%.
Keywords: HPLC, ethanol, caffeine, PFP-column, ecofriendly method